A Legal Perspective on The Transformation of Health Services with Artificial Intelligence - Siregar, Rospita Adelina (Universitas Katolik Soegijapranata Semarang, 2023)
Artificial Intelligence (AI) in medical services is expected to have a significant impact on the world of medicine. The research, which is a literature review, data collection, observation, analysis, is finally presented descriptively as a normative juridical study. The potential for AI to contribute the diagnostic process and even replacing the role of doctors is growing. Currently the use of AI has been utilized in medicine (registration, medical records, images, treatment, telemedicine, outbreak) and health resources.AI as an electronic agent operator is recognized as having a legal position, seen from Law number 19 of 2016 concerning electronic information and transactions (ITE Law) and PP 71/2019 concerning the implementation of electronic systems and transactions, regulating the limits of obligations and responsibilities of Electronic Agent organizers. In a trade context, hospitals are